Outcome of a research ethics training workshop among clinicians and scientists in a Nigerian university (2008)
Background: In Nigeria, as in other developing countries, access to training in research ethics is limited, due to weak social, economic, and health infrastructure. The project described in this article was designed to develop the capacity of academic staff of the College of Medicine, University of Ibadan, Nigeria to conduct ethically acceptable research involving human participants. Methods: Three in-depth interviews and one focus group discussion were conducted to assess the training needs of participants. A research ethics training workshop was then conducted with College of Medicine faculty. A 23-item questionnaire that assessed knowledge of research ethics, application of principles of ethics, operations of the Institutional Review Board (IRB) and ethics reasoning was developed to be a pre-post test evaluation of the training workshop. Ninety-seven workshop participants completed the questionnaire before and after the workshop; 59 of them completed a second post-test questionnaire one month after the workshop. Results: The trainees came from a multi-disciplinary background including medicine, nursing, pharmacy, social science and laboratory science. The mean scores for knowledge of the principles of research ethics rose from 0.67 out of 3 points at pre-test to 2.25 at post-test (p < 0.05). Also, 42% correctly mentioned one international guideline or regulation at pretest, with most of those knowing of the Declaration of Helsinki. Trainees' knowledge of the operations of an IRB increased from 6.05 at pre-test to 6.29 at post test out of 7 points. Overall, participants retained much of the knowledge acquired from the workshop one month after its completion. Conclusion: The training improved participants' knowledge of principles of research ethics, international guidelines and regulations and operations of IRBs. It thus provided an opportunity for research ethics capacity development among academic staff in a developing country institution.